(3eaGgje MOjKI aj EOGQI GdHfhc (B/s - (3YQeGf, RjGO eMeOs; (3GdNWjH, YGeQ s; (3YdG, JYje YHO GdbGOQs ((3YeGf(B: s (3OGQGdHOGjI(B, s, 2012)
(3CSGSjGJ aj GdeUGQa , JfXje GdeUGQa GdJLGQjI GdQFjSjI hhXGFagG h GdeRGjG GdJj JMbbgG aj JbOje GdNOeGJ GdMOjKI , GdSjhdI GdMGVQI h GdSjhdI THg GdfbOjI h GdSjhdI dCZQGV JdHjI GdbQhV h GdSdajGJ (B....(3, echfGJ SjGSI GdGbJQGV h eQGYGJ GdhGbYjI aj gPg GdSjGSI , GdYhGed GdeDKQI aj GdHfGA h GdJchjf GdJfXjej aj GdHfhc h eMOOGJ HfGA GdgjGcd GdJfXjejI , YedjGJ GdQbGHI h Jbhje GdCOGA ddefTBJ GdeGdjI h GdeUQajIs
Keywords: (3GdHfhcs; (3GdHfhc `` JfXje hEOGQIs; (3GdHfhc GdESdGejIs; (3GdHfhc GdJLGQjIs